P1506Prolonged and recurrent hospital admissions predict risk of cardiac implantable electronic device infections in hospitalized patients with bacteriaemia. (18th June 2020) - Esteves, A F; Marinheiro, R; Parreira, L; Mesquita, D; Fonseca, M; Farinha, J M; Pinheiro, A; Ferreira, J; Amador, P; Fonseca, N; Silvestre, I; Caria, R
Abstract: Background: As the use of Cardiac Implantable Electronic Devices (CIED) is expanding, the burden of device-related infections, particularly infectious endocarditis, is also increasing. Furthermore, with the increase in life expectancy, these devices are being implanted in patients who are older, with more serious co-morbidities and who are frequently hospitalized. Purpose: To assess incidence and predisposing factors for infective endocarditis (IE) in hospitalized patients with CIED and nosocomial bacteraemia. Methods: We performed a retrospective analysis of all hospitalized patients with CIED and positive blood cultures admitted to the Cardiology department between January 2012 and February 2019. Endocarditis was defined according to modified Duke criteria. We analyzed clinical parameters, device- and procedure-related characteristics, length of hospital stay and hospitalizations in the previous year. Results: 25 patients had positive blood cultures, 4 patients (16.0%) were diagnosed with infective endocarditis (median age 59.25 years, 75.0% male). Patients characteristics are displayed in the Table. In univariable analysis, the number and presence of hospitalizations in the previous year and the length of hospital stay was significantly associated with the possibility of endocarditis (respectively, OR 3.411, 95% CI 1.164-9.998, p-value 0.025; OR 18.000, 95% CI 1.375-235.686, p-value 0.028; and OR 1.047, 95% IC 1.001-1.096, p-value 0.046). Conclusion: In this group of patients with positive blood cultures during hospitalization, the possibility of CIED infection was predicted by the length of hospital stay and the presence and number of hospitalizations in the previous year.